2019
DOI: 10.1542/peds.2018-3664
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Abstinence Syndrome and Associated Neonatal and Maternal Mortality and Morbidity

Abstract: OBJECTIVES: We examined demographic characteristics and birth outcomes of infants with neonatal abstinence syndrome (NAS) and their mothers in Canada. METHODS: This retrospective, population-based, descriptive cross-sectional study of motherinfant dyads included all singleton live births in Canada (excluding Quebec), from 2005-2006 to 2015-2016 (N 5 2 881 789). Demographic characteristics, NAS, and neonatal and maternal morbidities were identified from delivery hospitalization data (including diagnostic codes)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Previous research has shown that compared with unexposed infants, infants with POE and NAS have an increased risk of low birth weight (Lisonkova et al 2019;Nørgaard et al 2015), preterm birth (birth before 37 weeks) (Alemu et al 2020;Brogly et al 2021;Corsi et al 2020;Maeda et al 2014) and stillbirth (Alemu et al 2020;Maeda et al 2014); and have poor fetal growth (Alemu et al 2020;Maeda et al 2014). The teratogenic effects of POE are still not well understood.…”
Section: Perinatal and Infant Health Outcomesmentioning
confidence: 99%
“…Previous research has shown that compared with unexposed infants, infants with POE and NAS have an increased risk of low birth weight (Lisonkova et al 2019;Nørgaard et al 2015), preterm birth (birth before 37 weeks) (Alemu et al 2020;Brogly et al 2021;Corsi et al 2020;Maeda et al 2014) and stillbirth (Alemu et al 2020;Maeda et al 2014); and have poor fetal growth (Alemu et al 2020;Maeda et al 2014). The teratogenic effects of POE are still not well understood.…”
Section: Perinatal and Infant Health Outcomesmentioning
confidence: 99%
“…Early life adversity is related to increased risks for developing many behavioral and psychiatric disorders [1]. A spectrum of prenatal, intrapartum, and postnatal episodes is likely to contribute to neurodevelopment via interactions with the individual's genotype to disrupt specific neural and psychophysiological system-related cognitive functions, thereby enhancing the risk for psychopathologies later in life [2,3]. Indeed, children exposed to perinatal opioid drugs appear to have a higher mortality rate after birth and suffer from neurodevelopmental consequences and behavioral problems [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Hospital charges due to NAS in the US rose from $190 M in 2000 to $720 M in 2009 [ 3 ]. In addition, for the dyad of mothers with NAS and their infants, maternal mortality is 6.4 times higher and neonatal mortality and/or severe mortality rates are 3.7 times higher than the corresponding rates of dyads without NAS [ 4 ].…”
Section: Introductionmentioning
confidence: 99%